(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article examines the modern mechanism of bank operations with plastic cards, gives the concept of the functioning of the electronic payment system, the concept of plastic cards, and also analyzes the main most profitable direction of the activity of Post Bank JSC - lending to individuals using plastic cards